Rehabilitation of the wrist and hand following sports injury - Jaworski, C. A.; Krause, M.; Brown, J. (Clinics in Sports Medicine, 2010)
In sports, wrist and hand injuries are commonplace. Too often, injuries to these areas can be under-treated and left for further complications to arise. While some injuries to the wrist and hand can be treated conservatively with immediate return to play, others require a more in-depth assessment prior to return to play. This article describes the most common wrist and hand injuries in sport, and provides information related to current treatment approaches.